The relationship between monetary benefits and job performance among the employees of the LGU of Guimbal - Geduspan, Jona
This study ams to determine whether or not monetary benefits affect job performance of the employee in the Local Government Unit (LGU) of Guimbal. The descriptive method was used in this study to determine the employee's perception towards monetary benefits and job performance. It utilized a total f twenty employee from different departments of the said LGU randomly selected as the respondents. The questionnaire was formulated as an aid to gather the needed primary data and information. The data were analyzed using percentaging and ranking. The study found out that the employees can perform better job if they received recognition or rewards in the hard work they render. They will be motivated to do their duties and responsibilities if they received an amount which can compensate with their physiological needs such as food, shelter and clothing.